PENGEMBANGAN GAME KAHOOT! BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATA PELAJARAN BAHASA INDONESIA SISWA KELAS IV SEKOLAH DASAR - Qonita Afriyani; Munaris; Rangga Firdaus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
games in improving students' critical thinking skills in the Indonesian language subject of grade IV students of SD Negeri 2 Perumnas Way Kandis. The development model used was 4D involving 31 students. The results showed that conventional methods caused boredom and saturation in learning, while local wisdom-based kahoot! games increased student engagement and understanding. Validation by material, language, and media experts ensured the feasibility of local wisdom-based kahoot! games with several revisions to improve the clarity of the display and language. The t-test showed a significant difference between the experimental class and the control class (Sig. 2-tailed = 0.000), N-Gain in the experimental class was 62.96% while in the control class it was 38.99% indicating high effectiveness. The average value increased from 58.25 (pre-test) to 84.77 (post-test). Thus, the kahoot! based on local wisdom has been proven to be an innovative solution in improving students' critical thinking skills.